Effective teaching strategies in "The Ron Clark Story" for teaching English as a foreign language - Floriasti, Tri Wahyuni; Destyana, Renasya (LITERA, 2023)
The need for improved language education approaches is critical given the current globalized world's growing demand for English language competency. Barriers based on language might prevent people from communicating and limit their chances. The goal of this study is to address the urgent need for creative and practical approaches to teaching foreign languages in order to enable students to get the language proficiency necessary for success in a globalized and multicultural society. The study explores effective teaching strategies in teaching and learning English as a foreign language, drawing insights from the movie "The Ron Clark Story." The research examines the alignment between the teaching strategies depicted in the movie and existing literature, specifically focusing on cognitive thinking and behavior. The research findings emphasize the significance of engaging in active social interactions, critical thinking, research, and evaluation to promote cognitive growth and improve language acquisition. The movie effectively showcases the positive impact of teaching strategies such as modeling, positive reinforcement, and structured learning on students' behavior. These findings imply that educators can implement these strategies to enhance cognitive growth and language learning and create a positive and engaging learning environment for English language learners in the classroom. The movie is a valuable resource and inspiration for educators seeking innovative approaches to teaching English as a foreign language. This research contributes to the existing body of knowledge on effective teaching strategies and their impact on cognitive thinking and behavior in the context of English language education.